Two-Dimensional Shear Wave Elastography of Normal Soft Tissue Organs in Adult Beagle Dogs; Interobserver Agreement and Sources of Variability - Jung, Jin-Woo; Je, Hyejin; Lee, Sang-Kwon; Jang, Youjung; Choi, Jihye (Frontiers in Bioengineering and Biotechnology, 2020)
Shear wave elastography (SWE) induces lateral shear wave through acoustic pulses of the transducer and evaluates tissue stiffness quantitatively. This study was performed to evaluate feasibility and reproducibility of two-dimensional shear wave elastography (2D SWE) for evaluation of tissue stiffness and to examine technical factors that affect shear wave speed (SWS) measurements in adult dogs. Nine healthy, 2 year-old, adult beagles with the median weight of 9.8 kg were included. In this prospective, experimental, exploratory study, 2D SWE (Aplio 600) from the liver, spleen, kidneys, pancreas, prostate, lymph nodes (submandibular, retropharyngeal, axillary, medial iliac, inguinal), submandibular salivary gland, and thyroid was performed in anesthetized beagles. Color map was drawn and SWS of each SWE were measured as Young's modulus (kPa) and shear wave velocity (m/s). The effect of measuring site, scan approach, depth, and anesthesia on SWE was assessed in abdominal organs by two observers independently. A total of 27 SWE examinations were performed in 12 organs by each observer. All SWS measurements were preformed successfully; however, SWE in the renal medulla could not be successfully conducted, and it was excluded from further analysis. Interobserver agreement of SWE was moderate to excellent in all organs, except for the left liver lobe at 10-15 mm depth with the intercostal scan. In the liver, there was no significant effect of the measuring site and scan approach on SWE. SWS of the liver and spleen tended to be higher with increasing the depth, but no significant difference. However, anesthesia significantly increased tissue stiffness in the spleen compared to awake dog regardless of the depth (P < 0.05). There was a significant difference in SWS according to the measuring site in the kidneys and pancreas (P < 0.001). 2D SWE was feasible and highly reproducible for the estimation of tissue stiffness in dogs. Measuring site and anesthesia are sources of variability affecting SWE in abdominal organs. Therefore, these factors should be considered during SWS measurement in 2D SWE. This study provides basic data for further studies on 2D SWE on pathological conditions that may increase tissue stiffness in dogs.